Conserved Composition of Nod Factors and Exopolysaccharides Produced by Different Phylogenetic Lineage Sinorhizobium Strains Nodulating Soybean - Wang, Dan; Couderc, François; Tian, Chang Fu; Gu, Wenjie; Liu, Li Xue; Poinsot, Verena (Frontiers in Microbiology, 2018)
The structural variation of symbiotic signals released by rhizobia determines the specificity of their interaction with legume plants. Previous studies showed that Sinorhizobium strains from different phylogenetic lineage had different symbiotic phenotype on certain cultivated soybeans. Whether they released similar or different symbiotic signals remained unclear. In this study, we compared their nod and exo gene clusters and made a detailed structural analysis of Nod factors and EPS by ESI-MS/MS and two dimensions NMR. Even if there are some differences among nod or exo gene clusters; they produced much conserved Nod factor and EPS compositions. The Nod factors consist of a cocktail of β-(1, 4)-linked tri-, tetra-, and pentamers of N-acetyl-D-glucosamine (GlcNAc). The C2 position on the non-reducing terminal end is modified by a lipid chain that contains 16 or 18 of carbon - with or without unsaturations- , and the C6 position on the reducing residue is decorated by a fucose or a 2-O-methylfucose. Their EPS are composed of glucose, galactose, glucuronic acid, pyruvic acid in the ratios 5:1:2:1 or 6:1:2:1. These findings indicate that soybean cultivar compatibility of Sinorhizobium strains does not result from Nod factor or EPS structure variations. The structure comparison of the soybean microbionts with other Sinorhizobium strains showed that Nod factor structures of soybean microbionts are much conserved, although there are no specific genes shared by the soybean microsymbionts. EPS produced by Sinorhizobium strains are much different from those of Bradyrhizobium. All above is consistent with the previous deduction that Nod factor structures are related to host range, when those of EPS are connected with phylogenetic.